2013
DOI: 10.1111/are.12217
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of basil (Ocimum basilicum) ethanolic extract supplementation diets against experimentalAeromonas hydrophilainfection in common carp (Cyprinus carpio)

Abstract: This study evaluated the effects of basil (Ocimum basilicum) leaves extract supplement on growth, blood parameters and resistance to Aeromonas hydrophila in Cyprinus carpio fingerlings. Basil leaves were mixed thoroughly with feed at 0, 100, 200, 400, 800 and 1600 mg kg À1 of diet and were fed in triplicate group for 2 months. At the end of this period, growth performance and survival were determined. Then fish were challenged intraperitoneally with A. hydrophila and mortalities were recorded up to 10 days pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 34 publications
1
17
0
1
Order By: Relevance
“…According to Amirkhani and Firouzbaksh (2015), diets supplemented with ethanol extract of O. basilicum increased the resistance of C. carpio against infection by A. hydrophila, due to improvement of the nonspecific immune system. This was also observed in L. rohita fed with diets containing M. indica and challenged with A. hydrophila (Sahu et al 2007).…”
Section: Acta Amazonicamentioning
confidence: 99%
See 1 more Smart Citation
“…According to Amirkhani and Firouzbaksh (2015), diets supplemented with ethanol extract of O. basilicum increased the resistance of C. carpio against infection by A. hydrophila, due to improvement of the nonspecific immune system. This was also observed in L. rohita fed with diets containing M. indica and challenged with A. hydrophila (Sahu et al 2007).…”
Section: Acta Amazonicamentioning
confidence: 99%
“…In Lates calcarifer, Allium sativum causes hematological changes and improves both oxygen transport and the immune response (Talpur and Ikhwanuddin 2012); Ocimum basilicum (basil) increases the resistance of Cyprinus carpio against infection by Aeromonas hydrophila (Amirkhani and Firouzbaksh 2015); and diets containing Mangifera indica (mango) kernel increase the resistance of L. rohita (Sahu et al 2007). Astaxanthin, a carotenoid pigment produced by some algae, and bacteria, was used at concentrations of 50 and 100 mg kg -1 in the diet of common carp C. carpio and, was found to stimulate growth, hematological alterations, immune response and specific bacterial disease protection (Jagruthi et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Different plants have shown improved growth and immune responses in different finfish and shellfish species such as Penaeusmonodon fed with Cyanodon dactylon, Picrorhiza kurooa, Aegle marmelos, Eclipta alba and Tinospor acordifoli (Citarasu et al, 2006), Tilapia niloticus fed with Foeniculum vulgare (Abd El-Hakim et al, 2010), Fenneropenaeus indicus fed with extracts of Adhatodavasika, Psoralea corylifolia, Ocimum basilicum, Quercus infectoria and Murraya koenigii (Velmurugan and Citarasu, 2010). Similarly, recent studies have shown improved growth in Channa punctatus, fed with Asparagus racemosus and Withania somnifera (Borkar et al, 2014), Macrobrachium rosenbergi fed with Alteranthera sessilis, Eclipta alba and Cissus quadrangularis (Radhakrishnan et al, 2014), Cyprinus carpio fed with Ocimum basilicum (Amirkhani and Firouzbakhsh, 2015), Macrobrachium malcomsoni fed with Alteranthera sessilis, Eclipta alba and Cissus quadrangularis (Radhakrishnan et al, 2015), Labeo rohita fed with extract of Mucuna pruriens (Ojha et al, 2014) and Houttuynia cordata (Garg et al, 2019), as well as to improve immunity and to cure various diseases (Citarasu et al, 2006;Sivaram et al, 2004).…”
Section: Introductionmentioning
confidence: 83%
“…These results are similar to those of Attalla (2009a), who reported that the use of forage as an additive significantly improved food intake, feed conversion ratio, and protein efficiency ratio. According to Amirkhani and Firouzbakhsh (2015), basil leaf extract at inclusion levels of 4% and 8% in fish feed improved growth and specific growth rate and the feed conversion ratio of common carp (Cyprinus carpio). The work of El-Dakar et al (2015) also showed that the addition of O. basilicum in the diet of Sparus aurata improved the FCR of fish fed the diet containing basil compared to control.…”
Section: Discussionmentioning
confidence: 99%